Strategies of the Manado State Christian Institute in Implementing Christian Cyber University-Distance Leaning - Wuwung, Olivia Cherly; Massang, Berdinata (AL-ISHLAH: Jurnal Pendidikan, 2024)
Distance learning at state Christian higher education institutions is something new. Therefore, this research aims to determine the appropriate strategy for implementing distance learning at Manado State Christian Institute. This research method uses a mixed method design, mixed method research that combines qualitative and quantitative data collection and analysis methods in one study and is carried out from April to June 2023. The method used by the respondents was the purposive sampling method. Respondents were selected from internal and external stakeholders, consisting of information technology and database unit staff, lecturers and students, and experts in the field of implementing distance learning. The instruments are the researchers themselves, interview guidelines, and questionnaires. Data analysis in the study uses SWOT and QSPM analysis methods. The results showed that based on the results of the IE analysis, the Manado State Christian Institute's position is in Quadrant II Growth Strategy (concentration through horizontal integration) with coordinate values (2.84, 3.39), which means that Manado State Christian Institute can improve its performance with internal and external resources. While the results of the QSPM analysis show that the three priority strategies for implementing distance learning are 1) Conducting benchmarking studies for the distance learning team with accredited excellence universities that offer distance education, 2) Strengthening the authority and responsibilities of distance education managers, and 3) Enhancing digital/cyber-based governance. This strategy is a priority strategy that will be implemented.